Incidence and Outcomes of Anterior Chamber Gas Bubble during Femtosecond Flap Creation for Laser-Assisted In Situ Keratomileusis - Sloan W. Rush; Philip Cofoid; Ryan B. Rush (Journal of Ophthalmology)
Purpose. To report the incidence and outcomes of anterior chamber gas bubble formation during femtosecond laser flap creation for laser-assisted in situ keratomileusis (LASIK). Methods. The charts of 2,886 consecutive eyes that underwent femtosecond LASIK from May 2011 through August 2014 were retrospectively reviewed. The incidence, preoperative characteristics, intraoperative details, and postoperative outcomes were analyzed in subjects developing anterior chamber gas bubble formation during the procedure. Results. A total of 4 cases (0.14%) developed anterior chamber gas bubble formation during femtosecond laser flap creation. In all four cases, the excimer laser was unable to successfully track the pupil immediately following the anterior chamber bubble formation, temporarily postponing the completion of the procedure. There was an ethnicity predilection of anterior chamber gas formation toward Asians (p=0.0055). An uncorrected visual acuity of 20/20 was ultimately achieved in all four cases without further complications. Conclusions. Anterior chamber gas bubble formation during femtosecond laser flap creation for LASIK is an uncommon event that typically results in a delay in treatment completion; nevertheless, it does influence final positive visual outcome.